2020
DOI: 10.1002/cpt.1909
|View full text |Cite|
|
Sign up to set email alerts
|

Prioritization of Anti‐SARS‐Cov‐2 Drug Repurposing Opportunities Based on Plasma and Target Site Concentrations Derived from their Established Human Pharmacokinetics

Abstract: There is a rapidly expanding literature on the in vitro antiviral activity of drugs that may be repurposed for therapy or chemoprophylaxis against severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). However, this has not been accompanied by a comprehensive evaluation of the target plasma and lung concentrations of these drugs following approved dosing in humans. Accordingly, concentration 90% (EC90) values recalculated from in vitro anti‐SARS‐CoV‐2 activity data was expressed as a ratio to the achiev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
149
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 116 publications
2
149
0
3
Order By: Relevance
“…A recent analysis of drugs proposed for repurposing as SARS-CoV-2 antiviral medicines revealed that very few of the proposed candidates achieved their target concentrations after administration of approved doses to humans [29]. Moreover, there have been several recent calls to integrate understanding of pharmacokinetic principles into COVID-19 drug prioritization[3032].…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis of drugs proposed for repurposing as SARS-CoV-2 antiviral medicines revealed that very few of the proposed candidates achieved their target concentrations after administration of approved doses to humans [29]. Moreover, there have been several recent calls to integrate understanding of pharmacokinetic principles into COVID-19 drug prioritization[3032].…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the virus was allowed to adsorb to cell monolayers [moi of 1] in 24-well plates for 1h, then parallel cultures were incubated at 37°C in 5% CO2 for 15, 30, 60 minutes, 2, 4, 6 hours prior to adding 15µM HCQ, 15µM TQ and 5µM RD, or negative control (assay media only). Concentrations were chosen to be approximately 5-fold higher than the EC50 in the 48h YR assay, except that for HCQ this was not possible due to cytotoxicity at concentrations ≥ 50 µM, so TQ and HCQ were [3,18,23]. It is apparent that the lack/modest level of activity of HCQ in both animal models and clinical studies [5,14] was not predicted from VERO cells and evidence of extensive lung penetration of HCQ.…”
Section: Manuscript Textmentioning
confidence: 99%
“…Currently, many ongoing trials have focused upon monotherapies that may provide insufficient drug exposures (1). Early HIV in vitro assay testing of antiretroviral compounds relied upon interpretation of in vitro EC 50 (effective concentration causing 50% of the maximal response) as a convenient measure for benchmarking clinical drug exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Several ad hoc and co-ordinated global screening programmes have been initiated, but with few exceptions (5), emergent literature to date has not robustly integrated an understanding of protein binding into screening and development of drugs for SARS-CoV-2. Indeed, none of the studies cited in a recent review of in vitro data sought to determine protein-adjusted activities using methods developed for other viruses (1). Revisiting the lessons learned over two decades ago in HIV is highly warranted.…”
Section: Introductionmentioning
confidence: 99%